2008
DOI: 10.3174/ajnr.a1242
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of11C-methionine Uptake in Low-Grade Gliomas and Correlation with Proliferative Activity

Abstract: BACKGROUND AND PURPOSE:The relationship of 11 C-methionine (MET) uptake and tumor activity in low-grade gliomas (those meeting the criteria for World Health Organization [WHO] grade II gliomas) remains uncertain. The aim of this study was to compare MET uptake in low-grade gliomas and to analyze whether MET positron-emission tomography (PET) can estimate tumor viability and provide evidence of malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 29 publications
(41 reference statements)
0
53
2
6
Order By: Relevance
“…[33][34][35][36] Some of those reports have shown positive correlations between the T/N ratio of 11 C-methionine PET and the Mib-1 labeling index, which reflects tumor proliferation capability. [34][35][36] On the other hand, others have shown a positive correlation between the T/N ratio and microvessel density, which is considered to reflect angiogenesis. 33 It should be noted that these nonstereotactic studies seem less accurate compared with stereotactic image-histology comparisons, as gliomas consist of heterogeneous tissues.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[33][34][35][36] Some of those reports have shown positive correlations between the T/N ratio of 11 C-methionine PET and the Mib-1 labeling index, which reflects tumor proliferation capability. [34][35][36] On the other hand, others have shown a positive correlation between the T/N ratio and microvessel density, which is considered to reflect angiogenesis. 33 It should be noted that these nonstereotactic studies seem less accurate compared with stereotactic image-histology comparisons, as gliomas consist of heterogeneous tissues.…”
mentioning
confidence: 99%
“…32,33 Previous reports have analyzed correlations among 11 C-methionine uptake, tumor proliferative ability, and angiogenesis. 22,[33][34][35][36] Several reports have been based on a comparison of the highest indices of each of these parameters. [33][34][35][36] Some of those reports have shown positive correlations between the T/N ratio of 11 C-methionine PET and the Mib-1 labeling index, which reflects tumor proliferation capability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,7,10,20,22,23 The diagnostic validity of PET for patients with brain tumors has been established for evaluating tumor malignancy, therapeutic response, or differentiation of tumor recurrence from tissue necrosis. However, few studies on spinal intramedullary lesions have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the diagnosis of central nervous system tumors, the usefulness of these radiotracers for brain tumors has been established for evaluating malignancies, therapeutic response, or differentiation of tumor recurrence from tissue necrosis. 1,2,7,10,20,22,23 However, investigations of spinal intramedullary tumors using PET remain sporadic, with only case reports or case series available to date. 5,6,8,11,13,[15][16][17]18 PET diagnosis of spinal intramedullary tumors can- 18 F]-fluorodeoxyglucose (FDG)-PET/CT was performed in 26 patients with spinal intramedullary lesions.…”
mentioning
confidence: 99%